Pre-harvest sprouting on high-level seed dormancy of bambara groundnut (Vigna subterranea) landraces - MARYATI SARI; SATRIYAS ILYAS; MOHAMAD RAHMAD SUHARTANTO; ABDUL QADIR (Society for Indonesian Biodiversity, 2021)
Abstract. Sari M, Ilyas S, Suhartanto MR, Qadir A. 2021. Pre-harvest sprouting on high-level seed dormancy of bambara groundnut (Vigna subterranea) landraces. Biodiversitas 22: 5617-5623. Bambara groundnut (Vigna subterranea (L.) Verdc.) is an underutilized crop. Therefore, its seed quality is not guaranteed. Pre-harvest sprouting (PHS) on bambara groundnut seeds can be found either due to the unpredictable rainfall or the late harvesting and plants are still in the field when rainfall. Conversely, seed dormancy causes a problem for planting. The objective of this research was to identify seed dormancy and PHS of four bambara groundnut landraces and other related seed characters. Four landraces (Madura, Sukabumi, Brown Sumedang and Tasikmalaya) were planted at the end of May 2017. Seeds were harvested at physiological maturity (130 days after planting) during the beginning of the wet season (early October 2017). The result showed that there were variations of PHS among landraces from 1% to 12%, and variations of seed dormancy rates from 62% to 82%. There were differences in seed color, seed size, tannin content, seed hardness, and imbibition rate. However, these characters could not clearly explain the diversities in PHS and seed dormancy. There was a high genetic diversity within Tasikmalaya landrace because this landrace had the highest PHS (12%) and the highest dormancy rate (82%) as well, although both characters are contradictory. This diversity needs further research, mainly to avoid the disadvantages due to PHS.